Analysis the impact of sun outage and satellite orbit at performance of the telkom 3S satellite communication system - Vi Bauty Riska Utami; Imam MPB; Shinta Romadhona (JURNAL INFOTEL, 2021)
Satellites of communication are located at altitude of thousands kilometers above the earth's surface, so the signal is transmitted by satellite to earth station is very susceptible to interference. Every March and September equinox or when the sun crosses the Earth's equator for several days, earth station occurs a naturally interference called by sun outage. At this time, satellite and the sun reach the closest distance because satellite's position is same direction with the sun. This interference makes the signal received by earth station weaken and even disappears due to temperature noise which increases drastically. Loss of signal on the downlink side caused by noise greatly affects to the performance of satellite communication system. This study aims to analyze the effect of sun outage and satellite orbit to determine sun outage period on the performance of Telkom 3S satellite communication system. The results obtained that indicate the signal quality is represented by degradation in the Carrier to Noise Ratio (C/N) from 14,777 dB to 6,0 dB, Energy bits per Noise Ratio (Eb/No) from 11,515 dB to 2,738 dB, and increase the Bit Error Rate (BER) from 8,29×10-7 to 11,08×10-3. In addition, sun outage makes lost of satellite communication traffic and affecting link availability to 99,855324%. Meanwhile, the result from satellite orbit calculation for sun outage period based on ITU-R S.1525 standard and based by satellite’s handbook. Keywords – Telkom 3S satellite, sun outage, C/N, Eb/No, BER, link availability, sun outage period.